1969
DOI: 10.1111/j.1399-3054.1969.tb07456.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Regulators and Wood Formation in Pinus silvestris

Abstract: The formation of new xylem in the spring is preceded by bud development. In decapitated pine stem the formation of xylem is arrested until the outgrowth of interfascicular buds takes place. When indole‐3yl‐acetic acid (IAA) is applied to the cut surfaces of decapitated stems it induces the formation of a xylem ring on the whole length of 5‐ycar old trees. Naphthaleneacetic acid (NAA) causes the formation of xylem; however, the width of the growth ring is several times broader at the point of application than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

1971
1971
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…However, Savidge et al . (178) found in Pinus contorta that the change in endogenous IAA level between activity and dormancy occurred mainly in the zone of developing xylem and that there was no evidence of a correlation between the number of cells per radial file in the cambial zone and the content of endogenous IAA in the cambial zone It has been demonstrated with many species that exogenous IAA promotes the radial enlargement of primary-walled cambial derivatives on the centripetal side of the cambial zone, i .e ., "tracheid radial enlargement," and, less decidedly, the thickening of the secondary wall in these cells, i .e ., "tracheid secondary wall thickening" (42, 59,68,78,92,93,131,151,171,175,186), which suggests that these developments are affected by the level of endogenous IAA . Involvement of endogenous IAA in the control of tracheid radial enlargement, but not in the regulation of tracheid secondary wall thickening, is indicated by the finding of a temporal correlation between declining cambial IAA levels and the annual transition from large-diameter thin-walled earlywood tracheids to narrow-diameter thick-walled latewood tracheids in Picea sitchensis (110), Pinus sylvestris (165), Pinus contorta (177,178), and Abies balsamea (193) .…”
Section: Physiological Significance Of Pgrs In the Cambial Region mentioning
confidence: 99%
See 2 more Smart Citations
“…However, Savidge et al . (178) found in Pinus contorta that the change in endogenous IAA level between activity and dormancy occurred mainly in the zone of developing xylem and that there was no evidence of a correlation between the number of cells per radial file in the cambial zone and the content of endogenous IAA in the cambial zone It has been demonstrated with many species that exogenous IAA promotes the radial enlargement of primary-walled cambial derivatives on the centripetal side of the cambial zone, i .e ., "tracheid radial enlargement," and, less decidedly, the thickening of the secondary wall in these cells, i .e ., "tracheid secondary wall thickening" (42, 59,68,78,92,93,131,151,171,175,186), which suggests that these developments are affected by the level of endogenous IAA . Involvement of endogenous IAA in the control of tracheid radial enlargement, but not in the regulation of tracheid secondary wall thickening, is indicated by the finding of a temporal correlation between declining cambial IAA levels and the annual transition from large-diameter thin-walled earlywood tracheids to narrow-diameter thick-walled latewood tracheids in Picea sitchensis (110), Pinus sylvestris (165), Pinus contorta (177,178), and Abies balsamea (193) .…”
Section: Physiological Significance Of Pgrs In the Cambial Region mentioning
confidence: 99%
“…In many species, the application of a relatively high concentration of IAA to vertically oriented stems induced the formation of compression wood (15, 59,68,78,93,124,131,151,171,186,190,206,216), which typically occurs on the lower sides of branches and inclined stems (218) . Furthermore, applying morphactin IT 3456, an inhibitor of IAA transport, to a vertically oriented or inclined stem promoted compression wood formation above the application point, and, in inclined stems, inhibited such formation below (142,144,187,230,231) .…”
Section: Physiological Significance Of Pgrs In the Cambial Region mentioning
confidence: 99%
See 1 more Smart Citation
“…Cambial division begins beneath the expanding buds and a wave of division spreads down the trunk (Priestley, Scott & Malins, 1933). Hejnowicz & Tomaszewski (1969) showed that in decapitated Pinus sylvestris shoots the formation of xylem is arrested until bud-flushing takes place. They found that there was no shortage of stored food which might limit xylem formation but a deficiency of IAA was clearly indicated.…”
Section: Endogenous Rhythmsmentioning
confidence: 99%
“…Badr et al (1970) também verificaram que a aplicação de GA (100, 250 e 500 mg L -1 ) promoveu a diferenciação do xilema em zonas recém-desenvolvidas de oliveiras, porém, segundo Hejnowicz & Tomaszewski (1969), há necessidade de GA e auxina em certo balanço para se obter máxima diferenciação do xilema em Pinus silvestris. Possivelmente esse efeito na diferenciação vascular está relacionado com os teores endógenos de giberelinas ativas e com a disponibilidade de receptores do hormônio vegetal.…”
Section: Efeitos Do Ga E Do Cepa Na Anatomia Do Nóunclassified